INFLUENCE OF COMBINATION ANTIHYPERTENSIVE THERAPY ON AORTA STIFFNESS PARAMETERS AND CENTRAL ARTERIAL PRESSURE IN HYPERTENSIVES WITH OBESITY - E. Yu. Shupenina; Yu. A. Vasyuk; E. A. Nesterova; S. V. Ivanova (Российский кардиологический журнал)
Aim. In the study we evaluated the influence of antihypertension therapy on 24-hour central BP and parameters of aorta stiffness in hypertensive patients with obesity.Material and methods. Totally, we included 80 patients with AH and obesity, at the age 35-55 y.o. All patients underwent clinical, laboratory and instrumental assessment, including office, home and 24-hour measurement of BP. All patients were randomized to 3 groups: 30 patients received fixed combination of trandolapril/ verapamil in daily dosage 2/180 mg, 25 — free combination of bisoprolol/indapamid 5-10/1,5 mg per day, 25 patients were taking fixed combination of perindopril/ amlodipine 5-10/5-10 mg per day. Follow-up period, in average, was 32 weeks.Results. All combinations studied significantly reduced central BP, but combination of bisoprolol/amlodipine was least effective. Only on perindopril/amlodipine there was significant reducing of aortal augmentation index (Δ% -4,1±8,7), that might be related to influence of the drug on HR. Analysis of daily dynamics of BP amplification of pulse BP, index of subendocardial blood circulation efficacy, pulse wave velocity, showed significant correlations between these parameters and HR. Thus, only prescription of pulse-reducing combinations of trandolapril/verapamil and bisoprolol/indapamid was followed by significant reduce of pulse wave velocity in aorta in patients with AH and obesity (Δ m/s -0,4±1,1; -0,4±0,7, resp.).Conclusion. Different influence of the studied combinations of antihypertension drugs on HR might be definitive for the improvement of aortic wall in AH patients and obesity.